BENEATH PATRIARCHAL LAYERS IN PAKISTANI SOCIETY: FEMINIST INSIGHTS INTO SHAMSIE AND MASROOR'S SELECTED SHORT STORIES (Contemporary Journal of Social Science Review, 2025)
This research examines the role of women in the male-dominated hierarchy, aiming to empower them to survive with dignity. In the current research, the foundation of patriarchy established by Gerda Lerner (1989) is applied as the basic theoretical framework. Voiceless women are provoked by patriarchy in several beliefs and doctrines. This research has been accomplished by textual analysis of Pakistani Short stories and focusing on various practices and occasions as reflected by Pakistani feminists to bring out the male-dominated systems. It depicts the way women have been exposed to treatment as commodities without considering their aspirations. Their disregard for patriarchal ideas can leave them without their lives as individuals. It also highlights that women are suppressed and persecuted by patriarchal frameworks. This study examines female figures in the selected literary works of Pakistani Short stories authored by Muneeza Shamsie’s Shahrazad’s Golden Leopard and The Monkey Wound by Hajra Masroor. Every character attempts to emancipate themselves from oppression leads to misogynistic violence.